Determination of radiation dose and low-dose protocol for digital chest tomosynthesis using radiophotoluminescent (RPL) glass dosimeters. (May 2020) - Tongkum, Sarawut; Suwanpradit, Petcharleeya; Vidhyarkorn, Sirachat; Siripongsakun, Surachate; Oonsiri, Sornjarod; Rakvongthai, Yothin; Khamwan, Kitiwat
Highlights: The selected low-dose protocol can substantially reduce the radiation dose compared to standard protocol. Low-dose protocol demonstrates acceptable pulmonary nodule detection capability. The effective dose of low-dose protocol is lower even compared to low-dose CT for lung cancer screening. The radiation dose in DTS can be reduced by reducing the dose ratio and increasing the cu-filter thickness. The nodule detection capability in DTS also depends on nodule size and the slice interval for image reconstruction. Abstract: Purpose: This study aimed to determine a low-dose protocol for digital chest tomosynthesis (DTS). Methods: Five simulated nodules with a CT number of approximately 100 HU with size diameter of 3, 5, 8, 10, and 12 mm were inserted into an anthropomorphic chest phantom (N1 Lungman model), and then scanned by DTS system (Definium 8000) with varying tube voltage, copper filter thickness, and dose ratio. Three radiophotoluminescent (RPL) glass dosimeters, type GD-352 M with a dimension of 1.5 × 12 mm, were used to measure the entrance surface air kerma (ESAK) in each protocol. The effective dose (ED) was calculated using the recorded total dose-area-product (DAP). The signal-to-noise ratio (SNR) was determined for qualitative image quality evaluation. The image criteria and nodule detection capability were scored by two experienced radiologists. The selected low-dose protocol was further applied in a clinical study with 30 pulmonary nodule follow-up patients. Results: The average ESAK obtained from the standard default protocol was 1.68 ± 0.15 mGy, while an ESAK of 0.47 ± 0.02 mGy was found for a low-dose protocol. The EDs for the default and low-dose protocols were 313.98 ± 0.72 µSv and 100.55 ± 0.28 µSv, respectively. There were small non-significant differences in the image criteria and nodule detection scoring between the low-dose and default protocols interpreted by two radiologists. The effective dose of 98.87 ± 0.08 µSv was obtained in clinical study after applying the low-dose protocol. Conclusions: The low-dose protocol obtained in this study can substantially reduce radiation dose while preserving an acceptable image quality compared to the standard protocol.